Tìm x:
a) \(^{x^2-\frac{5}{14}.x=0}\)
b) \(2^x+2^{x+2}=160\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, x( x - 3) - ( x + 2)( x - 1) = 3
<=> x2 - 3x - x2 + x - 2x + 2 = 3
<=> x2 - 3x - x2 + x - 2x = 3 - 2
<=> -4x = 1
<=> x =\(-\frac{1}{4}\)
Vậy_
b, \(x-\frac{x-1}{5}+\frac{x+2}{6}=4+\frac{x+1}{3}\)
\(\Leftrightarrow\frac{30x}{30}-\frac{\left(x-1\right)6}{30}+\frac{\left(x+2\right)5}{30}=\frac{120}{30}+\frac{\left(x+1\right)10}{30}\)
=> 30x - 6x + 6 + 5x + 10 = 120 + 10x + 10
<=> 30x - 6x + 5x - 10x = 120 + 10 - 6 - 10
<=> 19x = 114
<=> x = 6
Vậy _
b: \(\dfrac{5}{7}-\dfrac{2}{3}\cdot x=\dfrac{4}{5}\)
=>\(\dfrac{2}{3}x=\dfrac{5}{7}-\dfrac{4}{5}=\dfrac{25-28}{35}=\dfrac{-3}{35}\)
=>\(x=-\dfrac{3}{35}:\dfrac{2}{3}=\dfrac{-3}{35}\cdot\dfrac{3}{2}=-\dfrac{9}{70}\)
c: \(\dfrac{1}{2}x+\dfrac{3}{5}x=-\dfrac{2}{3}\)
=>\(x\left(\dfrac{1}{2}+\dfrac{3}{5}\right)=-\dfrac{2}{3}\)
=>\(x\cdot\dfrac{5+6}{10}=\dfrac{-2}{3}\)
=>\(x\cdot\dfrac{11}{10}=-\dfrac{2}{3}\)
=>\(x=-\dfrac{2}{3}:\dfrac{11}{10}=-\dfrac{2}{3}\cdot\dfrac{10}{11}=\dfrac{-20}{33}\)
d: \(\dfrac{4}{7}\cdot x-x=-\dfrac{9}{14}\)
=>\(\dfrac{-3}{7}\cdot x=\dfrac{-9}{14}\)
=>\(\dfrac{3}{7}\cdot x=\dfrac{9}{14}\)
=>\(x=\dfrac{9}{14}:\dfrac{3}{7}=\dfrac{9}{14}\cdot\dfrac{7}{3}=\dfrac{3}{2}\)
a: \(\Leftrightarrow\left(x+2\right)\left(12-x\right)=0\)
\(\Leftrightarrow x\in\left\{-2;12\right\}\)
b: \(\Leftrightarrow\left(2x+5\right)\left(x-1\right)=0\)
\(\Leftrightarrow x\in\left\{-\dfrac{5}{2};1\right\}\)
a: =>x+5>0
hay x>-5
b: =>2x+1<0
hay x<-1/2
c: =>(x-1)(x-4)>0
=>x>4 hoặc x<1
a: \(\Leftrightarrow x^2+10x+25-x^2+4x=55\)
=>14x=30
hay x=15/7
b: \(\Leftrightarrow\left(x-7\right)\left(x-3\right)=0\)
hay \(x\in\left\{7;3\right\}\)
a) \(\left(x-2\right)^2-\left(x^2-3x\right)=9\)
\(\Rightarrow x^2-4x+4-x^2+3x-9=0\)
\(\Rightarrow-x-5=0\)
=> x = -5
b) \(\left(5x-2\right)^2=\left(4-x\right)^2\)
\(\Rightarrow25x^2-10x+4-16+8x-x^2=0\)
\(\Rightarrow24x^2-2x-12=0\)
\(\Rightarrow12x^2-x-6=0\)
\(\Rightarrow\left[{}\begin{matrix}x=-\dfrac{2}{3}\\x=\dfrac{3}{4}\end{matrix}\right.\)
c) \(x^2-4x-5=0\)
=> (x - 5).(x + 1) = 0
=> x = 5 hoặc x = -1
a: =>1/3x+2/5x-2/5=0
=>11/15x-2/5=0
=>11/15x=2/5
=>x=2/5:11/15=2/5*15/11=30/55=6/11
b: =>-5x-1-1/2x+1/3=x
=>-11/2x-2/3-x=0
=>-13/2x=2/3
=>x=-2/3:13/2=-2/3*2/13=-4/39
c: (x+1/2)(2/3-2x)=0
=>x+1/2=0 hoặc 2/3-2x=0
=>x=1/3 hoặc x=-1/2
d: 9(3x+1)^2=16
=>(3x+1)^2=16/9
=>3x+1=4/3 hoặc 3x+1=-4/3
=>3x=1/3 hoặc 3x=-7/3
=>x=1/9 hoặc x=-7/9